Small genetic variation affecting mRNA isoforms associated with marbling and meat color in beef cattle - Muniz, Maria Malane Magalhães [UNESP]; Fonseca, Larissa Fernanda Simielli [UNESP]; dos Santos Silva, Danielly Beraldo [UNESP]; Magalhães, Ana Fabrícia Braga [UNESP]; Ferro, Jesus Aparecido [UNESP]; Chardulo, Luiz Artur Loyola [UNESP]; Baldi, Fernando [UNESP]; Cánovas, Angela; de Albuquerque, Lucia Galvão [UNESP] (Springer Nature, 2022)
The aim of this study was to identify mRNA isoforms and small genetic variants that may be affecting marbling and beef color in Nellore cattle. Longissimus thoracis muscle samples from 20 bulls with different phenotypes (out of 80 bulls set) for marbling (moderate (n = 10) and low (n = 10) groups) and beef color (desirable (n = 10) and undesirable (n = 9) group) traits were used to perform transcriptomic analysis using RNA sequencing. Fourteen and 15 mRNA isoforms were detected as differentially expressed (DE) (P-value ≤ 0.001) between divergent groups for marbling and meat color traits, respectively. Some of those DE mRNA isoforms have shown sites of splicing modified by small structural variants as single nucleotide variant (SNV), insertion, and/or deletion. Enrichment analysis identified metabolic pathways, such as O2/CO2 exchange in erythrocytes, tyrosine biosynthesis, and phenylalanine degradation. The results obtained suggest potential key regulatory genes associated with these economically important traits for the beef industry and for the consumer.
Keywords: Deletion; Genetic variants; Insertion; Nellore breed; RNA sequencing; Single nucleotide variant (SNV)